1991
DOI: 10.1007/bf00280098
|View full text |Cite
|
Sign up to set email alerts
|

Buccal versus intravenous nitroglyerin in unstable angina pectoris

Abstract: The clinical syndrome of unstable angina includes patients with the first onset of angina, change in a previous stable pattern or the development of chest pain at rest. Administration of intravenous nitroglycerin is established therapy in unstable angina. Buccal nitroglycerin has been introduced as an alternative means of administering nitroglycerin, which provides relief of anginal pain within 2 to 3 min and a sustained effect for 3 to 5 h. Twenty-nine patients admitted to the coronary care unit due to unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…One small randomized trial compared intravenous NTG with buccal NTG and found no significant difference in the control of ischemia. 308 An overview of small studies of NTG in MI from the prefibrinolytic era suggested a 35% reduction in mortality rates; 309 in contrast, both the Fourth International Study of Infarct Survival (ISIS-4) 310 and Gruppo Italiano per lo Studio della Sopravvivenza nellinfarto Miocardico (GISSI-3) 311 trials formally tested this hypothesis in patients with suspected MI in the reperfusion era and failed to confirm this magnitude of benefit. However, these large trials are confounded by frequent prehospital and hospital use of NTG in the "control" groups.…”
Section: Nitratesmentioning
confidence: 99%
“…One small randomized trial compared intravenous NTG with buccal NTG and found no significant difference in the control of ischemia. 308 An overview of small studies of NTG in MI from the prefibrinolytic era suggested a 35% reduction in mortality rates; 309 in contrast, both the Fourth International Study of Infarct Survival (ISIS-4) 310 and Gruppo Italiano per lo Studio della Sopravvivenza nellinfarto Miocardico (GISSI-3) 311 trials formally tested this hypothesis in patients with suspected MI in the reperfusion era and failed to confirm this magnitude of benefit. However, these large trials are confounded by frequent prehospital and hospital use of NTG in the "control" groups.…”
Section: Nitratesmentioning
confidence: 99%
“…One small randomized trial compared intravenous NTG with buccal NTG and found no significant difference in the control of ischemia (308). An overview of small studies of NTG in MI from the prefibrinolytic era suggested a 35% reduction in mortality rates (309); in contrast, both the Fourth International Study of Infarct Survival (ISIS-4) (310) and Gruppo Italiano per lo Studio della Sopravvivenza nell'infarto Miocardico (GISSI-3) (311) trials formally tested this hypothesis in patients with suspected MI in the reperfusion era and failed to confirm this magnitude of benefit.…”
Section: Nitratesmentioning
confidence: 99%
“…One small randomized trial compared intravenous NTG with buccal NTG and found no significant difference in the control of ischemia. 314 An overview of small studies of NTG in MI from the prefibrinolytic era suggested a 35% reduction in mortality rates 315 ; in contrast, both the Fourth International Study of Infarct Survival (ISIS-4) 316 and Gruppo Italiano per lo Studio della Sopravvivenza nell'infarto Miocardico (GISSI-3) 317 trials formally tested this hypothesis by guest on http://circ.ahajournals.org/ Downloaded from in patients with suspected MI in the reperfusion era and failed to confirm this magnitude of benefit. However, these large trials are confounded by frequent prehospital and hospital use of NTG in the "control" groups.…”
Section: Nitratesmentioning
confidence: 99%